High prevalence of insulin resistance among Brazilian chronic hepatitis C patients - Villar, Livia Melo (2017)
Fundação Oswaldo Cruz. Instituto Oswaldo Cruz. Laboratório de Hepatites Virais. Rio de Janeiro, RJ. Brasil.